ANTIBACTERIAL ACTIVITY PROFILE OF MANGROVE ENDOPHYTIC FUNGI ISOLATED FROM BERAU REGENCY, INDONESIA - Sukarno (BRIN - Badan Riset dan Inovasi Nasional, 2022)
Mangrove endophytic fungi have the potential to produce secondary metabolites with antibacterial properties. This study aimed to obtain endophytic mold isolates associated with mangrove plants and their antimicrobial activity. Seventeen endophytic molds were isolated from 7 mangrove species originating from Berau, East Kalimantan, Indonesia. Three extracts from the mold isolates OJ-B, OJ-Bu, and 6Xg-Bh showed the highest antibacterial activity with an inhibition zone of 9.63–25.4 mm and with MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) values ??of around 0.625–5 and 2.5–10 mg mL–1, respectively. LC-MS (liquid chromatography-mass spectrometry) analysis identified several compounds with antibacterial potential, namely beauvericin, choline, nicotinic acid, pyridoxine, quinoline, cyclo (phenylalanyl-prolyl), fusarin c, oleamide and borrelidin. The 3 species were molecularly identified as Diaporthe phaseolorum, Fusarium proliferatum and Phomopsis sp. Thus, the endophytic molds from several of the mangrove species produced bioactive compounds as antibacterial.